HAS1high cancer associated fibroblasts located at the tumor invasion front zone promote oral squamous cell carcinoma invasion via ECM remodeling - Wanyong Jin; Qiuya Yu; Liyuan Yu; Ting Zhou; Xiren Wang; Wanqiu Lu; Xiaoxin Zhang; Liang Ding; Qingang Hu; Yanhong Ni (Journal of Experimental & Clinical Cancer Research)
Abstract Background Although tumor cell heterogeneity between the tumor center (TC) and invasion front (IF) of oral squamous cell carcinoma (OSCC) is well documented, the morphological, molecular, and functional characteristics of cancer-associated fibroblasts (CAFs) in these regions remain poorly understood. Methods We examined hematoxylin and eosin (H&E)–stained OSCC sections to assess CAF morphology and correlation with patient prognosis. We then isolated paired CAFs from the tumor center (CAFTC) and invasion front (CAFIF) of four OSCC patients and compared their ECM-remodeling activity and pro-tumorigenic effects on OSCC cells. Furthermore, RNA sequencing identified differentially expressed genes between CAFTC and CAFIF. Finally, based on RNA-seq findings, we knocked down hyaluronan synthase 1 (HAS1) in CAFIF to evaluate its role in extracellular matrix (ECM) remodeling and tumor invasion. Results Compared to CAFTC, CAFIF exhibited a plump cell morphology and were associated with shorter disease-free survival. Functionally, CAFIF showed higher ECM-remodeling activity and more effective ability for promoting OSCC invasion and lymph node metastasis than CAFTC. RNA-seq identified HAS1 was significantly upregulated in CAFIF, promoting hyaluronic acid (HA) production and ECM remodeling. HAS1 knockdown in CAFIF diminished ECM remodeling and attenuated the ability of CAFIF to promoting OSCC invasion. Conclusion CAFIF with plump cell morphology showed pro-invasive abilities, driven in part by HAS1 overexpression and ECM remodeling, suggesting that targeting HAS1-driven ECM remodeling could be a promising therapeutic strategy.